Gaya Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di Sekolah Dasar : Studi Kasus di SDN Kota Medan - Dinda Boru Anugrah; Tria Amanda Nasution; Adinda Mutia Rahma Siregar; Mairani; Winara; Ibrahim Gultom (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The principal’s leadership plays a strategic role in improving the quality of education in elementary schools. In the era of educational transformation and rapid technological advancement, school principals are required to implement adaptive, innovative, and inspirational leadership models. One of the leadership approaches considered effective in improving the quality of learning is transformational leadership. This study aims to analyze the transformational leadership style of the principal in improving the quality of learning at SDN 064037 Medan City. This research employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, educational staff, and several students. Data analysis was conducted using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. The results showed that the principal implemented transformational leadership through strengthening school vision and mission, motivating teachers, improving teacher professionalism, conducting academic supervision, and creating a collaborative school culture. The principal also encouraged the use of innovative learning methods and technology-based learning to improve student engagement and learning outcomes. The implementation of transformational leadership positively impacted teacher performance, student participation, learning discipline, and overall school climate. However, several obstacles were identified, including limited educational facilities, differences in teacher competencies, and administrative burdens. The study concludes that transformational leadership significantly contributes to improving the quality of learning in elementary schools and supports the realization of effective and student-centered education.